Comparison of Efficacy of Glycyrrhiza Glabra (Licorice Extract) and Vitamin E in Decreasing Fibrosis Score in patients with Non-Alcoholic Fatty Liver Disease - Muhammad Abdullah, Bilal Aziz, Tazeen Nazar, Noor-Un-Nisaa Zia, Hussain Farooq, Numreen Nazar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the efficacy of Glycyrrhiza glabra and vitamin E in decreasing fibrosis score in patients with non-alcoholic fatty liver disease (NAFLD). Method: This randomized controlled trial was carried out in the Medical Wards of Mayo Hospital/King Edward Medical University, Lahore. Two hundred and twelve patients with NAFLD were divided via random assignment into Group A that was given 800IU of vitamin E per day and Group B that received Glycyrrhiza Glabra in a dose of 10 mg per day. Both groups received treatment for 3 months and were re-evaluated monthly for improvement in fibrosis scores and liver transaminases. Data was analyzed using version 26.0 of SPSS. Results: Out of 212 patients, 53.4% were male and 46.6% were female. Mean age of patients in Group A was 35.8±14.26 and 41.93±14.2 in Group B. Fibrosis score in Group A decreased from 0.19± 1.02 to -0.14± 1.09 while reduction in Group B was from 0.29± 0.93 to -0.67± 0.97 (p-value <0.000). Only patients in Group B showed significant reduction in alanine transaminase (ALT 62.3± 15.3 to 57.2± 14.58, p-value <0.000). In lowering fibrosis score, vitamin E was effective in 11.3% of patients, whereas Glycyrrhiza glabra was effective in 34% patients (p-value 0.000). Practical Implication: With the global increase in the cases of NAFLD, it has become imperative to devise new treatment strategies to overcome this burden. No definitive treatment modality provides an ultimate cure for these patients. This study proves a superior role of Glycyrrhiza glabra (licorice extract) in terms of lowering fibrosis score and reduction of ALT levels. Conclusion: Both Glycyrrhiza glabra and vitamin E were effective in lowering fibrosis scores in patients with NAFLD, however, Glycyrrhiza glabra was more superior in terms of efficacy than vitamin E and also caused a considerable decrease in ALT levels. Keywords: Glycyrrhiza glabra, Vitamin E, Fibrosis Score, Non-alcoholic fatty liver disease